An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Experimental study of seepage and water-rock heat transfer in granite fracture under chemical action - Ruotao Liu; Guan Rong; Bowen Li; Zhongjie Yu; Huqi Zhang; Qinyan Qiu (European Journal of Environmental and Civil Engineering, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Identification of concentrated seepage pathways integrating hydrogeological mechanisms and data-driven modeling: a case study of the Baihetan hydropower station - Guan Rong; Huqi Zhang; Maiyong Jiang; Qinyan Qiu; Shilong Chen (Engineering Geology, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Rapid in-situ recovery of starved anammox consortia: Metabolic stimulation and microbial synergy driven by organics and oxygen - Yihao Qiu; Chenrong Gu; Jiaqi Han; Jiaqi Zhang; Qi Zhang; Rong Li; Xiao-Ming Ji (Environmental Research, 2026)

A 3D sp2-carbon-conjugated hydrogen-bonded COF platform for reductive gold capture and photocatalytic detoxification of a chemical warfare simulant - Xiao-Yi Fan; Xiu Wang; Yong Zhang; Wei-Bin Qiu; Wei-Rong Cui (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Corrigendum to “State-selective engineering in luminescent metal-organic frameworks: Ligand-to-ligand charge transfer activates superior photocatalytic sterilization in Wei River” [J Hazard Mater 500 (2025) 140448] - Liang Qiu; Yajie Zhang; Baiyu Wu; Wenqiong Liu; Yiwen Xie; Jing He; Kerang Huang; Jianlong Wang; Rong Wang (Journal of Hazardous Materials, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Biochar aging-driven cadmium release in paddy soils: Mechanistic insights into adsorption capacity loss and biochar feedstock-specific risks - Ze-ning Yu; Xiao-qing Zhang; Fei-mei Chen; Rong-liang Qiu; Kuan Zhou; Xin-xian Long (Journal of Environmental Sciences, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Ultra-rapid global ionospheric modeling method incorporating AOT-GAN virtual VTEC observations under partial missing data conditions - Rong Wang; Yibin Yao; Liang Zhang; Peng Chen; Jian Kong; Liangcai Qiu; Fucai Tang (Journal of Geodesy, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Settling and dewatering characteristics of super absorbent polymer treated fine-grained dredged sediment waste - Yupeng Cao; Jie Yin; Xinzhuang Cui; Zhehao Qiu; Shuai Zhang; Rong Wang (Journal of Soils and Sediments, 2026)

Trichoderma maomingense (Sordariomycetes, Hypocreaceae), a New Species Isolated From Bamboo in Guangdong Province, China - Dai‐Yan Huang; Qiu‐Rong Huang; Zhang‐Yong Dong; Mei Luo (New Zealand Journal of Botany, 2026)
Trichoderma species are widely distributed across various habitats worldwide and play significant roles in the biological control of plant diseases, plant growth promotion, and soil improvement. In this study, a novel Trichoderma species was isolated from dead culms of Bambusa cerosissima McClure in Maoming City, Guangdong Province, China. Based on morphological characteristics and multigene phylogenetic analyses of translation elongation factor 1 α ( tef1‐α ), nuclear internal transcribed spacer of rDNA region (ITS), and RNA polymerase second largest subunit ( rpb2 ) by both maximum likelihood (ML) and bayesian inference (BI) approaches, three isolates were identified as a new species within the Koningii‐clade, named Trichoderma maomingense sp. nov. The distinctions between this new species and its closely related taxa are discussed in detail.

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Characteristics of VOCs emissions and environmental impact assessment of typical automobile manufacturing enterprises in Beijing, China - Yinquan Qiu; Xinyu Zhang; Rong Sun; Houjian Yang; Ming Liu; Lianhai Ren; Pan Wang (Air Quality, Atmosphere & Health, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Significant generational effects of tetracyclines upon the promoting plasmid-mediated conjugative transfer between typical wastewater bacteria and its mechanisms - Lingling Rong; Baoyin Zhang; Hongmu Qiu; Hailin Zhang; Jiayin Yu; Qing Yuan; Ligui Wu; Hong Chen; Yuanmin Mo; Xiaoming Zou; Xubiao Luo (Water Research, 2025)

Bioactive constituents from Salacia obovatilimba as potential in vitro hSGLT2 inhibitors - Zhi-Yong Jiang; Lin Chen; Hong-Xi Xie; Jun-Jie Hao; Rong Chen; Chun-Qiu Huang; Hong-Lei Zhang; Ai-Xue Zuo (Phytochemistry, 2025)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

State-selective engineering in luminescent metal-organic frameworks: Ligand-to-ligand charge transfer activates superior photocatalytic sterilization in Wei River - Liang Qiu; Yajie Zhang; Baiyu Wu; Wenqiong Liu; Yiwen Xie; Jing He; Kerang Huang; Jianlong Wang; Rong Wang (Journal of Hazardous Materials, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Exploring the dual role of anti-nutritional factors in soybeans: a comprehensive analysis of health risks and benefits - Dakai Di; Shudong He; Rong Zhang; Kuan Gao; Min Qiu; Xingjiang Li; Hanju Sun; Sophia Xue; John Shi (Critical Reviews in Food Science and Nutrition, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Microplastics impair wound healing via NAT10-mediated epigenetic dysregulation of FASN-PI3K/AKT signaling - Feng-Jie Shen; Wei-Nan Cao; Xue-Chun Han; Qiu-Yue Pan; Yuan Wang; Rong Zhang; Gang Wei; Jin-Kui Yang (NanoImpact, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Insights from structural characterization for understanding isolation and impact of roasting on allergenic potential of sesame Oleosins - Dakai Di; Rong Zhang; Huimei Li; Min Qiu; Suwei Jiang; Shuizhong Luo; Hanju Sun; Shudong He (Food Chemistry, 2025)

The long-term dynamics of biodiversity and stability of the diatom community under climate warming in a Tibetan alpine lake - Yanjie Zhao; Rong Wang; Hengshuai Qiu; Wenxiu Zheng; Enlou Zhang; Xiangdong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Experimental study on mechanical behavior of basalt under different freeze–thaw conditions - Bowen Li; Ruotao Liu; Qinyan Qiu; Huqi Zhang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Comparative life cycle assessment of traditional and emerging methods for high concentration organic wastewater treatment - Yilin Yuan; Fengming Zhang; Yuxin Qiu; Yuejie Zhao; Weiqing Rong (Science of The Total Environment, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

Versatile room temperature phosphorescence polymer with luminophore content as low as 0.05 wt% - Wen Wen Deng; Ze Ping Zhang; Min Zhi Rong; Ming Qiu Zhang (Chemical Engineering Journal, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Ecological response to global changes in Lake Genco, a remote alpine lake on the Southeast Tibetan Plateau, over the past two centuries - Yanjie Zhao; Rong Wang; Hengshuai Qiu; Jianan Zheng; Kexin Zhu; Wenxiu Zheng; Xiangdong Yang; Enlou Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Significant terrigenous dilution affected biogenic deposits in the Bay of Bengal during the last deglaciation to glaciation - Zhuoya Qiu; LanLan Zhang; Yiping Yang; Yun Huang; Rong Xiang; Zhong Chen (Global and Planetary Change, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Remote-Sensing Estimation of Upwelling-Frequent Areas in the Adjacent Waters of Zhoushan (China) - Teng Xiao; Jiajun Feng; Zhongfeng Qiu; Rong Tang; Aibo Zhao; Kapo Wong; Jin Yeu Tsou; Yuanzhi Zhang (Journal of Marine Science and Engineering, 2024)
Upwelling, which mixes deep and surface waters, significantly enhances the productivity of surface waters and plays a critical role in marine ecosystems, especially in key fishing areas like Zhoushan. This study utilized merged sea surface temperature data and an upwelling edge detection algorithm based on temperature gradients to analyze the characteristics of upwelling in Zhoushan and the Yangtze River Estuary over the past 28 years. The results indicate that upwelling in Zhoushan begins in April, peaks in July, gradually weakens, and disappears by October. The phenomenon is most pronounced during the summer months (June to August), with significant spatial distribution differences in April and September. Notably, high probability values of upwelling centers and core areas are mainly concentrated near Ma’an Island, Zhongjieshan Island, and Taohua Island. In these areas, upwelling remains stable during the summer, forming a unique “footprint” distribution pattern, and these are also the locations of the Zhoushan National Marine Ranch. From April to August, the extent of the upwelling area gradually decreases and stabilizes. These findings emphasize the frequent upwelling activity around Zhoushan and its significant contribution to the formation of local fisheries. Additionally, considering that the formation of natural upwelling in the East China Sea depends on the southern monsoon, the study suggests establishing artificial upwelling systems during periods unfavorable for natural upwelling, based on high probability areas, to enhance fishery yields and support the development of local fisheries.

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Ent-atisane diterpenoids from Euphorbia wallichii and their anti-influenza A virus activity - Jie Zhang; Xiao-Jia Guo; Xiao-Juan Chen; Rong-Rong Zhang; Bai-Ping Ma; Zhong-Qiu Liu (Phytochemistry, 2024)

Inputs of terrestrial dissolved organic matter in dam reservoirs during precipitation: impact on water quality and management - Rong Hao; Xingle Ning; Yaru Zhou; Ruicheng Ma; Xueshuai Zhang; Guohong Qiu; Ronggui Hu (Natural Hazards, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Subchannel thermal–hydraulic analysis of a wire-wrapped 19-pin rod bundle in the NACIE-UP facility - Rong Zhang; Dalin Zhang; Yu Liang; Jinshun Wang; Jian Deng; Xisi Zhang; Zhixin Niu; Wenxi Tian; Suizheng Qiu; Qi Luo (Annals of Nuclear Energy, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Investigation on effect evaluation of seepage control system of large underground powerhouse of the Baihetan hydropower station - Qinyan Qiu; Guan Rong; Huqi Zhang; Wenfu Chen; Yaosheng Tan (Tunnelling and Underground Space Technology, 2023)

Rethinking terrestrial dissolved organic matter in dam reservoirs before mixing: Linking photodegradation and biodegradation and the phenanthrene binding behavior - Yupeng Wu; Xueshuai Zhang; Rong Hao; Yaru Zhou; Guohong Qiu; Ronggui Hu; Yantun Song (Science of The Total Environment, 2023)

A strategy to prepare low-temperature curable photosensitive polyimide with good comprehensive performance - Shan Huang; Xialei Lv; Xingwang Lai; Jinhui Li; Yao Zhang; Siyao Qiu; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Seepage field analysis and evaluation of seepage control effect at the dam foundation of Baihetan Hydropower Station - Huqi Zhang; Guan Rong; Qinyan Qiu; Wenfu Chen; Yaosheng Tan (Bulletin of Engineering Geology and the Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Analysis of reservoir slope deformation during initial impoundment at the Baihetan Hydropower Station, China - Lida Xu; Guan Rong; Qinyan Qiu; Huqi Zhang; Wenfu Chen; Zhiheng Chen (Engineering Geology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Energy and exergy assessments of supercritical water oxidation of wet organic wastes under hydrothermal flames with a Y-shape reactor for power generation - Fengming Zhang; Yang He; Yuxin Qiu; Weiqing Rong (Fuel, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Efficacy of Aidi injection combined with chemotherapy, radiotherapy or chemoradiotherapy for unresectable esophageal cancer treatment: A meta-analysis and systematic review of 29 randomized controlled trials based on Asian populations (China) - Jinsheng Huang; Teng Fan; Yuming Rong; Xujia Li; Qi Jiang; Jun Kan; Huijuan Qiu; Qi Quan; Bei Zhang; Guifang Guo (European Journal of Clinical Pharmacology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

“Sandwich-like” electrospinning fiber-based molecularly imprinted membrane constructed with electrospun polyethyleneimine as the multifunction interlayer for the selective separation of shikimic acid - Yao Zhu; Yuting Dai; Jian Rong; Tao Zhang; Songlin Xue; Dongya Yang; Jianming Pan; Fengxian Qiu (Chemical Engineering Journal, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Silencing circ_0074371 inhibits the progression of sepsis-induced acute kidney injury by regulating miR-330-5p/ELK1 axis - Qiu-yuan Wang; Rong-rong Zhang; Long Cui; Ya-ping Sun (Mammalian Genome, 2022)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Circular RNA circ_Cabin1 promotes DNA damage in multiple mouse organs via inhibition of non-homologous end-joining repair upon PM2.5 exposure - Huixian Zeng; Meizhen Li; Qiuhan Hua; Yufei Liu; Yueting Shao; Qinqin Diao; Yihui Ling; Han Zhang; Miaoyun Qiu; Jialu Zhu; Xun Li; Rong Zhang; et al. (Archives of Toxicology, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Shortening the sgRNA-DNA interface enables SpCas9 and eSpCas9(1.1) to nick the target DNA strand - Rong Fan; Zhuangzhuang Chai; Sinian Xing; Kunling Chen; Fengti Qiu; Tuanyao Chai; Jin-Long Qiu; Zhengbin Zhang; Huawei Zhang; Caixia Gao (Science China Life Sciences, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

METTL1 overexpression is correlated with poor prognosis and promotes hepatocellular carcinoma via PTEN - Qiu-Hong Tian; Mei-Fang Zhang; Jin-Sheng Zeng; Rong-Guang Luo; Yang Wen; Jun Chen; Liu-Gen Gan; Jian-Ping Xiong (Journal of Molecular Medicine, 2019)

Synergistic effects of stromal cell-derived factor-1α and bone morphogenetic protein-2 treatment on odontogenic differentiation of human stem cells from apical papilla cultured in the VitroGel 3D system - Min Xiao; Jun Qiu; Rong Kuang; Beidi Zhang; Wei Wang; Qing Yu (Cell and Tissue Research, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Water environment early warning index system in Tongzhou District - Xiu-ju Zhang; Ning Qiu; Wen-Rong Zhao; Huan An; Julius Lissa Tommy (Natural Hazards, 2015)

Determination of selected pharmaceuticals in tap water and drinking water treatment plant by high-performance liquid chromatography-triple quadrupole mass spectrometer in Beijing, China - Mei-Quan Cai; Rong Wang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2015)

Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Assessing the real value of farmland in China - Rong Hu; Dao-chi Qiu; De-ti Xie; Xin-ya Wang; Lin Zhang (Journal of Mountain Science, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Protective effect of whey protein hydrolysates against hydrogen peroxide-induced oxidative stress on PC12 cells - Qiu-Xiang Zhang; Yu-Fang Ling; Zhen Sun; Li Zhang; Hui-Xin Yu; Samuel Mburu Kamau; Rong-Rong Lu (Biotechnology Letters, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Assay and characterization of an osmolarity inducible promoter newly isolated from Bacillus subtilis - Wei-Wei Zhang; Qiu-Rong Gao; Ming-Ming Yang; Hui Liu; Dun Wang (Molecular Biology Reports, 2012)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Expression analysis and genetic mapping of three SEPALLATA-like genes from peach (Prunus persica (L.) Batsch) - Yong Xu; Lin Zhang; Hua Xie; Yan-Qiu Zhang; M. Margarida Oliveira; Rong-Cai Ma (Tree Genetics & Genomes, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)